Sampling harmful benthic dinoflagellates: Comparison of artificial and natural substrate methods - Tester, Patricia A.; Kibler, Steven R.; Holland, Wiliam C.; Usup, Gires; Vandersea, Mark W.; Chui , Pin Leaw; Lim , Po Teen; Larsen, Jacob; Mohammad Noor, Normawaty; Faust, Maria A.; R. Litaker, Wyane (Elsevier B.V., 2014)
This study compared two collection methods for Gambierdiscus and other benthic harmful algal bloom (BHAB) dinoflagellates, an artificial substrate method and the traditional macrophyte substrate method. Specifically, we report the results of a series of field experiments in tropical environments designed to address the correlation of benthic dinoflagellate abundance on artificial substrate and those on adjacent macrophytes. The data indicated abundance of BHAB dinoflagellates associated with new, artificial substrate was directly related to the overall abundance of BHAB cells on macrophytes in the surrounding environment. There was no difference in sample variability among the natural and artificial substrates. BHAB dinoflagellate abundance on artificial substrates reached equilibrium with the surrounding population within 24 h. Calculating cell abundance normalized to surface area of artificial substrate, rather than to the wet weight of macrophytes, eliminates complications related to the mass of different macrophyte species, problems of macrophyte preference by BHAB dinoflagellates and allows data to be compared across studies. The protocols outlined in this study are the first steps to a standardized sampling method for BHAB dinoflagellates that can support a cell-based monitoring program for ciguatera fish poisoning. While this study is primarily concerned with the ciguatera-associated genus Gambierdiscus, we also include data on the abundance of benthic Prorocentrum and Ostreopsis cells.